Arbitration, a tool for good coexistence - José Manuel Fanjul Díaz (ADIDE Federación, 2008)
Conflict situations are real facts effectively verified both in state schools and in private schools, as well as stubbornly supported by statistic reports. We can look aside, but this only contributes to worsen this trend. Consequently, people with responsibility in education must do our best to provide suitable solutions to this worrying problem. Arbitration and mediation arise then as two efficient possibilities. A thorough reflection about the first of them is developed with highlight on the route to follow when putting arbitration into practice, a process not yet tackled in articles of this kind.